2019
DOI: 10.2478/sgem-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of randomly distributed polypropylene fiber reinforcement on the shear behavior of sandy soil

Abstract: The inclusions of geosynthetic materials (fibers, geomembranes and geotextiles) is a new improvement technique that ensures uniformity in the soil during construction. The use of tension resisting discreet inclusions like polypropylene fibers has attracted a significant amount of attention these past years in the improvement of soil performance in a cost-efficient manner. A series of direct shear box tests were conducted on unreinforced and reinforced Chlef sand with different contents of fibers (0, 0.25, 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…In contrast, the fiber strips initially orientated at 120 • did not improve and, in some cases, even weakened the sand, as indicated by the peak strength ratios smaller than or equal to 1.0. Similar results were also obtained by [12,14]. As mentioned in Section 1, the influence of initial orientation angle of fiber on sand strength may be explained by the stress mobilization in fibers.…”
Section: Peak Strengthsupporting
confidence: 85%
“…In contrast, the fiber strips initially orientated at 120 • did not improve and, in some cases, even weakened the sand, as indicated by the peak strength ratios smaller than or equal to 1.0. Similar results were also obtained by [12,14]. As mentioned in Section 1, the influence of initial orientation angle of fiber on sand strength may be explained by the stress mobilization in fibers.…”
Section: Peak Strengthsupporting
confidence: 85%
“…Figures (17)(18)(19)(20) presents total displacement shading obtained from Plaxis 3D output at failure for various cases.…”
Section: E Bearing Capacity Failure Modementioning
confidence: 99%
“…The effect of using PP fiber on soil bearing capacity was investigated by [18]. The experimental results show that the addition of polypropylene fibers improves the mechanical properties.…”
Section: Introduction mentioning
confidence: 99%
“…The addition of fibers increased the internal friction angle and cohesion of the clay. Benziane et al (2019) carried out a series of direct shear box tests to compare unreinforced and reinforced soil with different contents of fibers. The experimental results showed that the mechanical characteristics was improved with the addition of polypropylene fibers.…”
Section: General Properties Of Polypropylene Fibersmentioning
confidence: 99%